2014
DOI: 10.3389/fnhum.2014.00881
|View full text |Cite
|
Sign up to set email alerts
|

Single motor unit firing behavior in the right trapezius muscle during rapid movement of right or left index finger

Abstract: Background: Computer work is associated with low level sustained activity in the trapezius muscle that may cause development of trapezius myalgia. Such a low level activity may be attention related or alternatively, be part of a general multi joint motor program providing stabilization of the shoulder joint as a biomechanical prerequisite for precise finger manipulation. This study examines single motor unit (MU) firing pattern in the right trapezius muscle during fast movements of ipsilateral or contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Piotrkiewicz and Kuraszkiewicz ( 2014 ) investigated the relationship between duration of motoneuron AHP and confirmed an earlier observation by Kernell ( 1964 ) that motoneurons with shorter AHPs discharge doublets more easily. Doublets were also mentioned in Søgaard et al ( 2014 ). Triplet discharges have been reported by Piotrkiewicz and Kuraszkiewicz ( 2014 ) and the authors speculate on the possible mechanisms to explain this pattern.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Piotrkiewicz and Kuraszkiewicz ( 2014 ) investigated the relationship between duration of motoneuron AHP and confirmed an earlier observation by Kernell ( 1964 ) that motoneurons with shorter AHPs discharge doublets more easily. Doublets were also mentioned in Søgaard et al ( 2014 ). Triplet discharges have been reported by Piotrkiewicz and Kuraszkiewicz ( 2014 ) and the authors speculate on the possible mechanisms to explain this pattern.…”
mentioning
confidence: 72%
“…Six papers deal with motoneuron discharge related to pathology. Søgaard et al ( 2014 ) recorded electromyographic activity bilaterally from upper trapezius muscles. They observed a tonic low level motor unit activity and suggested that such activity, whether it is built into the motor program to stabilize the limbs or results from stress of paying attention during computer work, may be the underlying cause of myalgia observed in computer workers.…”
mentioning
confidence: 99%
“…The latter could be approached with the use of elbow support, which would decrease the need for anticipatory shoulder stabilisation. Maintaining work-related local activity is believed to impair cellular mechanisms, leading to increased input to free nociceptive nerve endings [34]. In conclusion, both headache research and research in physiology and ergonomics support evidence on the involvement and impairment of subparts of the trapezius muscles in continuous daily, and especially workrelated activities, leading to prolonged nociceptive input and hypersensitivity.…”
Section: Lifestyle-related Physical Factors and Resourcesmentioning
confidence: 91%
“…Piotrkiewicz and Kuraszkiewicz (2014) investigated the relationship between duration of motoneuron AHP and confirmed an earlier observation by Kernell (1964) that motoneurons with shorter AHPs discharge doublets more easily. Doublets were also mentioned in Søgaard et al (2014). Triplet discharges have been reported by Piotrkiewicz and Kuraszkiewicz (2014) and the authors speculate on the possible mechanisms to explain this pattern.…”
mentioning
confidence: 95%
“…Søgaard et al (2014) recorded electromyographic activity bilaterally from upper trapezius muscles. They observed a tonic low level motor unit activity and suggested that such activity, whether it is built into the motor program to stabilize the limbs or results from stress of paying attention during computer work, may be the underlying cause of myalgia observed in computer workers.…”
mentioning
confidence: 99%